Body weight control and energy expenditure. (August 2018) - Fonseca, Danielle Cristina; Sala, Priscila; de Azevedo Muner Ferreira, Beatriz; Reis, Jessica; Torrinhas, Raquel Susana; Bendavid, Itai; Linetzky Waitzberg, Dan
Summary: Body composition has great importance in the value of energy expenditure. Reduced energy expenditure plays an important role in the development of obesity by decreasing resting energy expenditure, energy activity, diet-induced thermogenesis, or a combination of all of these components. It thus contributes to positive energy balance and subsequent weight gain. Obesity, therefore, can be considered, among other aspects, the consequence of an energy imbalance; that is, energy intake greater than that spent in a certain period. In order to have stability of body weight and body composition it would be necessary for energy intake to correspond to energy expenditure. Regarding the comparison of energy expenditure between non-obese and obese individuals, the results point to a differentiated behavior of obese individuals. However, it has not yet been possible to identify which specific energy expenditure component contributes most to this differentiated behavior can (resting energy expenditure, energy expenditure during physical activity or food thermogenesis). Thus, it is important to standardize the techniques for the evaluation of these parameters in order to improve the reproducibility of the results.